1990
DOI: 10.1116/1.576602
|View full text |Cite
|
Sign up to set email alerts
|

Formation of cubic boron nitride films by arc-like plasma-enhanced ion plating method

Abstract: Articles you may be interested inResidual compressive stress induced infrared-absorption frequency shift of hexagonal boron nitride in cubic boron nitride films prepared by plasma-enhanced chemical vapor deposition

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

1993
1993
2013
2013

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 150 publications
(15 citation statements)
references
References 1 publication
0
15
0
Order By: Relevance
“…On the other hand, a number of studies on BN film growth on metallic substrates using PVD or CVD techniques revealed the development of an alloy layer at the substrate/film interface. 159,160 On that account, the formation of metal nitrides or borides which does not maintain the desired lattice match may hamper heteroepitaxial c-BN film growth on metallic substrates. A few reports have also been presented on the deposition of heteroepitaxial c-BN films on highly oriented wurtzite AlN films.…”
Section: Effect Of Substratesmentioning
confidence: 99%
“…On the other hand, a number of studies on BN film growth on metallic substrates using PVD or CVD techniques revealed the development of an alloy layer at the substrate/film interface. 159,160 On that account, the formation of metal nitrides or borides which does not maintain the desired lattice match may hamper heteroepitaxial c-BN film growth on metallic substrates. A few reports have also been presented on the deposition of heteroepitaxial c-BN films on highly oriented wurtzite AlN films.…”
Section: Effect Of Substratesmentioning
confidence: 99%
“…On the other hand, a number of studies on BN film growth on metallic substrates using PVD and CVD techniques revealed the development of an alloy layer at the substrate-film interface. 36,37 On that account, the formation of metal nitrides or borides which do not maintain the desired lattice match may hamper heteroepitaxial c-BN film growth on metallic substrates.…”
Section: Selection Of Appropriate Substrates For Direct Nucleatiomentioning
confidence: 99%
“…Both n-and p-type dopability of c-BN makes this sample important in the manufacture of electronic devices [1][2][3]. In a recent work [4], c-BN has been reported to be an ideal substrate for the fabrication of high temperature UV and blue light emitting diodes (LEDs) [1,5,6] and laser diodes (LDs) [7].…”
Section: Introductionmentioning
confidence: 99%